Estimation of Mangrove Carbon Standing-stock along the Coast of Kailolo Village, Central Maluku: Implications for Climate Change Mitigation - Naflah Dafi Al-Fiyah Ombi; Rahman Rahman; Juliana Wilmiena Tuahatu (Politeknik Negeri Sambas, 2025)
This study aims to estimate the carbon stock and sequestration potential of the mangrove ecosystem along the Hitapory Coast, Kailolo Village, Central Maluku, as a critical step in supporting climate change mitigation efforts. Data collection was conducted at five stations using the quadrat transect method to measure vegetation density, stem diameter, and identify mangrove species. Biomass analysis was performed using allometric equations appropriate for the dominant species. The results indicate a total carbon stock of 330.74 tons C/ha, comprising 227.19 tons C/ha of above-ground carbon (AGC) and 103.55 tons C/ha of below-ground carbon (BGC). The estimated carbon sequestration, expressed in CO₂ equivalents, was 1,212.72 tons CO₂e/ha, with the dominant contribution from Sonneratia alba at 1,187.50 tons CO₂e/ha, while the lowest contribution was from Rhizophora stylosa at 10.76 tons CO₂e/ha. These findings highlight the significant role of the local mangrove ecosystem as an effective carbon sink. Therefore, the conservation and sustainable management of mangroves are essential to support both national and global carbon emission reduction strategies. Furthermore, the study presents an opportunity to develop policies centered on blue carbon trading as an innovative mechanism for climate change mitigation.